Strategi Manajemen Sarana dan Prasarana Untuk Meningkatkan Minat Belajar Siswa I MTSS SKB 3 Menteri Pembangunan Lidah Tanah - Lubis, Arif Abdul Gani; Siahaan, Amiruddin; Tarigan, Mardinal (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The research entitled "Facilities and Infrastructure Management Strategies to Increase Students' Interest in Learning at MTSS SKB 3, Minister for Development of Tongue Tanah" aims to analyze facilities and infrastructure management strategies in order to increase students' interest in learning at MTSS SKB 3, Minister for Development of Tongue Tanah. Interest in learning is an important factor in the success of the educational process, and adequate facilities and infrastructure can play a big role in encouraging this interest. This research uses a qualitative descriptive approach with data collection techniques through interviews, observation and documentation. The research results show that the management of facilities and infrastructure at MTSS SKB 3 Ministers has been managed well, but there are still several challenges in meeting optimal facility needs. The strategies implemented include improving more varied learning facilities, routine maintenance of existing facilities, as well as optimizing the use of classrooms and laboratories for teaching and learning activities. This improvement in facilities and infrastructure has been proven to increase students' interest in learning, which is reflected in their activity during the learning process, both individually and in groups. This research suggests that the management of Islamic education at MTSS SKB 3 Minister of Development of Lidah Tanah continues to innovate in managing educational facilities and increase participation of all school elements to achieve optimal educational goals.